Neonatal outcomes from in vitro fertilization-conceived pregnancies - Ashfahani Imanadhia; Risma Kerina Kaban; Adhi Teguh Perma Iskandar; Reynaldo Rahima Putra; Ressa Hana Natasa (Indonesian Pediatric Society, 2023)
Background In vitro fertilization (IVF) shows potential to improve pregnancy success, especially for infertile couples. This technique has some risks for neonates in the perinatal period and may affect their future health. Objective To investigate the characteristics and clinical outcomes of neonates from IVF-conceived pregnancies. Methods This retrospective study was conducted in neonates from IVF-conceived pregnancies from January to December 2021 at Bunda Women’s and Children’s Hospital, Jakarta. We gathered data from medical records about maternal age and morbidity, gravidity, gestational age, method of delivery, multiple gestation, also neonates’ significant profiles like prematurity, birth weight, Apgar score, and morbidities in perinatal period. We would like to investigate the characteristics and clinical outcomes of neonates born from IVF-conceived pregnancies program. Results There were 361 neonates whose mothers underwent IVF included in this study. Most mothers were ?35 years (70.9%) and on their first pregnancy (69.2%). Maternal complicating factors were premature contractions (16.6%), premature rupture of membranes (8.3%), and twin pregnancy (31.5%). About 98.6% of deliveries were performed by caesarean section and from IVF-conceived pregnancies program most 61.2% neonates were born at full term gestation (61.2%). Preterm deliveries occurred at a mean gestational age of 34.4 (SD 2.4) weeks. Subjects’ mean birth weight was 2,800.2 (SD 640.3) grams, with 26.3% in the low-birth-weight category. Most neonates (93.0%) were appropriate weight for gestational age and had good Apgar scores in the first minute (92.2%) and fifth minute (99.7%). However, 24.3% of neonates needed intensive care (NICU) with morbidities. The longest length of NICU stay was 100 days, with mortality of 7.9% of NICU-treated infants. Conclusion In our setting, most neonates from the IVF program were born with good outcomes, although preterm birth rate, low birth weight, need for NICU care, and mortality rate were quite high. Further study is needed to evaluate long-term outcomes of IVF neonates.